Cerium phosphate-based inhibitor for smart corrosion protection of WE43 magnesium alloy. (1st January 2021) - Calado, Lénia M.; Taryba, Maryna G.; Morozov, Yegor; Carmezim, Maria J.; Montemor, M.F.
Highlights: Efficient corrosion protection of WE43 conferred by Ce(DEHP)3 . Improved performance of Ce(DEHP)3 in intact and damaged coatings. Self-healing of corrosion activity in the presence of Ce(DEHP)3 . pH-dependant activation of Ce(DEHP)3. Abstract: Ce(DEHP)3 (cerium tri(bis(2-ethylhexyl)phosphate)) is proposed as a self-healing corrosion inhibitor for WE43. The use of Ce(DEHP)3 in a 3.90 ± 0.54 µm hybrid epoxy-silane coating led to an improvement of the coating barrier properties. The presence of the inhibitor increased the corrosion resistance, and Electrochemical Impedance Spectroscopy tests carried out in 0.5 M NaCl revealed low frequency impedance modulus (0.01 Hz) around 10 9 Ω∙cm 2 . The pH-dependant self-healing effect of Ce(DEHP)3 was evidenced by localized electrochemical techniques, which revealed inhibition of corrosion propagation in artificial defects and decreased net cathodic current densities compared to an unmodified reference coating. Protective behaviour of Ce(DEHP)3 was related to the combined action of the cerium and organophosphate moieties of this inhibitor, in addition to the protective role of yttrium species derived from the yttrium present in the WE43 magnesium alloy. Graphical abstract: Image, graphical abstract